Responses of bone cells to microinjury - Mulcahy, Lauren Elizabeth (Trinity College (Dublin, Ireland). Department of Mechanical and Manufacturing Engineering, 2012)
Microdamage in bone has been implicated as a principal stimulator of bone remodeling through the release of numerous biochemical factors. Such factors initiate the bone resorbing and bone forming potential of the constitutive cells of the Basic Multicellular Unit (BMU). Further to this, an accumulation of microdamage has been implicated in potentiating the risk of fracture in osteoporotic patients, and current treatments for osteoporosis have been thought to exacerbate the risk of fracture through suppression of the normal microdamage mediated response in bone. The overall goal of this study was to determine the effects of microdamage, in terms of microinjury, most notably the impact of injury size, on the biochemical pathways involved in stimulating bone remodeling, and subsequently, the cellular response to microinjury. Additionally, the effects of bisphosphonates, which are commonly used therapeutics in the treatment of osteoporosis, on bone remodeling activities, were also determined.
Keywords: Mechanical and Manufacturing Engineering, Ph.D.; Ph.D. Trinity College Dublin